(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Online marketing communications are moving toward interactions between individual recipients and consumers rather than being directed from a marketing organization to masses of consumers. It is now possible for an individual to be just as efficient in broadcasting information, both positive and negative, about an organization as it is for a large corporation to promote itself. The social networking that allows the quick and easy dissemination of information and mis-information is in part a product of changes in online communication channels, but these communication channels are in part enabled by such social networking. From a marketing perspective, we are at a pioneering stage in understanding how these work. This article suggests an infrastructure that could be useful in studying how online communication channels are emerging and how they might evolve in the future. The elements of this infrastructure are core/technological, competitive/commercial, political/regulatory, and social.